Effectiveness of Exercise Therapy on the Muscle Strength, Ankle Joint Mobility and Gait Speed of Patient Diabetes Mellitus: Literature Review - Wahyuna Sahmar; Elly Lilianty Sjattar; Saldy Yusuf (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Introduction: Lower extremity ulcers represent a serious and costly complication of diabetes mellitus. Many factors contribute to the development of diabetic foot, such as limited joint mobility of the ankle and foot level, impaired muscular performance and reduced gait speed. Several studies discuss the effects of planned and structured exercise or physical movements on leg muscle strength and ankle joint mobility.Aim: This literature study aims to analyse the effect of an experimental protocol of exercise therapy on joint mobility, muscular strength and gait speed in a group of diabetic subjects. Method: This study explores quantitative published in the electronic databases: PubMed, Science Direct, and Proquest. Using a search strategy, we identified 131 potentially relevant articles. Fourteen studies were included in the final analysis.Result: This study obtained 14 journals that consist of RCT, quasi-experimental study, and cross-sectional. This literature study showed that significant post-intervention improvements in limited joint mobility of the ankle and foot level, impaired muscular performance and reduced gait speed for participants who received exercise therapy compared to the control groups.Conclusions: These results indicate that program of exercise therapy significantly improves joint mobility, muscular strength and walking speed in diabetic patients and community nurses can apply that to improve community health status.